A Randomized-Controlled Trial Using Point of Care Ultrasound to Evaluate Volunteer Patients in the Emergency Department Versus a Manikin Simulator for Improving Knowledge and Confidence of Hypotension and Shock in Medicine Sub-Internship Students - Patel B; Dobiesz VA; Goldsmith AJ; Montgomery MW; Osman NY; Pelletier SR; Miller MS; Shields HM (Advances in Medical Education and Practice)
Badar Patel,1,2 Valerie A Dobiesz,3,* Andrew J Goldsmith,3,4,* Mary W Montgomery,1 Nora Y Osman,1 Stephen R Pelletier,5 Michael S Miller,1 Helen M Shields1 1Department of Medicine, Brigham and Women’s Hospital, Boston, MA, USA; 2Division of Cardiovascular Medicine, Beth Israel Deaconess Medical Center, Boston, MA, USA; 3Department of Emergency Medicine, Brigham and Women’s Hospital, Boston, MA, USA; 4Department of Emergency Medicine, Lahey Hospital, Burlington, MA, USA; 5Office of Medical Education, Harvard Medical School, Boston, MA, USA*These authors contributed equally to this workCorrespondence: Helen M Shields, Brigham and Women’s Hospital, 75 Francis St, Boston, MA, 02115, Tel +1 (617) 678-6077, Email hmshields@bwh.harvard.eduAim: Point of Care Ultrasound (POCUS) excels in the assessment of patients with hypotension and shock. Whether using real patients or a manikin simulator to teach POCUS skills is preferable is not completely clear. We designed a randomized-controlled trial to compare these two different teaching methods of POCUS.Methods: We enrolled 47 medical students on an internal medicine sub-internship in this randomized-controlled trial. Twenty-four students were randomly assigned to the experimental group to learn from volunteer patients in the emergency department (ED), and 23 were randomly assigned to the control group to learn from a manikin simulator in a simulation center. All students received a didactic workshop focused on hypotension and shock, followed by supervised learning from either volunteer patients in the ED or a manikin simulator in a simulation center. Student knowledge and confidence were assessed through a pre-survey before the workshop, post-survey after the workshop, and a 3-month longitudinal survey after both the workshop and supervised POCUS learning were completed. The primary end point was assessment of student knowledge and confidence at the 3-month longitudinal time period.Results: At the 3-month longitudinal survey, there was no statistical difference in the primary end point of questions correctly answered by students in the experimental group compared to those in the control group (88% vs 86.5%, p = 0.713, NS), and no statistical difference in reported confidence between students in the experimental group from those in the control group (4.22 vs 4.10, p = 0.846, NS).Conclusion: In this randomized-controlled trial using POCUS to assess hypotension and shock, there were no significant differences in learner knowledge and confidence between students in the ED experimental group learning from volunteer patients versus the control group learning from a manikin simulator indicating that the methods may be equally effective in teaching POCUS.Keywords: simulation, medical education, point of care ultrasound, volunteer patients